Rational design and synthesis of sandwich-like reduced graphene oxide/Fe2O3/N-doped carbon nanosheets as high-performance anode materials for lithium-ion batteries. (15th February 2021) - Wang, Jitong; Yang, Xiaojuan; Wang, Yongbang; Jin, Shuangling; Cai, Wendi; Liu, Baishan; Ma, Cheng; Liu, Xiaojun; Qiao, Wenming; Ling, Licheng
Graphical abstract: Highlights: Sandwich-like RGO/Fe2 O3 /N-doped carbon nanosheet was well designed and constructed. Nanometer Fe2 O3 are anchored within the sandwich structure of graphene nanosheet and nitrogen doping carbon layer. Every component of the composite nanosheet produces a synergistic effect for promoting the electrochemical performance. RGO/Fe2 O3 /N-doped carbon nanosheet exhibits excellent cycling stability and high rate capacity. Abstract: To cope the challenges of poor conductivity and volume change for iron oxide, sandwich-like reduced graphene oxide/Fe2 O3 /N-doped carbon nanosheets are well designed and constructed via a two-step process through the combination of graphene-oriented hydrothermal method and the sol–gel coating technology. Nanometer Fe2 O3 with a size of 10 nm is anchored within the sandwich structure composed of graphene nanosheet and a thin nitrogen doping carbon layer. Such unique structure can not only reduce the length of pathway for lithium ion diffusion and electron transport but also greatly alleviate the volume expansion as well as offer more surface active sites for electrochemical process, leading to a superior cycle stability and a high rate capability. The obtained nanosheet delivers an outstanding lithium storage capacity of 1116.7 mA h g −1 after 100 cycles at current density of 500 mA g −1 and an excellent rate capability of 547.4 mA h g −1 at high current density of 4 A g −1 . Furthermore, full cell is fabricated using the nanosheet as anode and commercial LiFePO4 as cathode, which exhibits stable cycling performance, indicating good applicability of the anode. This work proposes a novel strategy to synthesize composites which could be further applied to the development of transition metal oxides and carbon composites as anode for lithium ion batteries.